2014
DOI: 10.1002/dvdy.24172
|View full text |Cite
|
Sign up to set email alerts
|

Pard3 regulates contact between neural crest cells and the timing of Schwann cell differentiation but is not essential for neural crest migration or myelination

Abstract: Background Schwann cells, which arise from the neural crest, are the myelinating glia of the peripheral nervous system. During development neural crest and their Schwann cell derivatives engage in a sequence of events that comprise delamination from the neuroepithelium, directed migration, axon ensheathment and myelin membrane synthesis. At each step neural crest and Schwann cells are polarized, implying important roles for molecules that create cellular asymmetries. In this work we investigated the possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 62 publications
(88 reference statements)
0
28
0
1
Order By: Relevance
“…To determine if Sox10:zFucci is neural crest‐specific while NCCs are delaminating and migrating, we crossed the Sox10:zFucci line with the Sox10:mRFP line, which is commonly used to label NCCs (Blasky, Pan, Moens, & Appel, ; Leigh et al, ). We performed time‐lapse confocal microscopy of Sox10:zFucci; Sox10:mRFP‐dual positive embryos from 14 to 23 hours post‐fertilization (hpf) or 13 to 28 hpf (Figure b–e; Supporting Information Movies S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…To determine if Sox10:zFucci is neural crest‐specific while NCCs are delaminating and migrating, we crossed the Sox10:zFucci line with the Sox10:mRFP line, which is commonly used to label NCCs (Blasky, Pan, Moens, & Appel, ; Leigh et al, ). We performed time‐lapse confocal microscopy of Sox10:zFucci; Sox10:mRFP‐dual positive embryos from 14 to 23 hours post‐fertilization (hpf) or 13 to 28 hpf (Figure b–e; Supporting Information Movies S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…Wildtype (WT) strains include AB, TAB, and EKK lines (ZIRC) and transgenic lines include sox10: eGFP (Dutton et al, 2008), tg(sox10: memRFP ) vu234 (Blasky et al, 2014) and tg(hsp70l:shha-eGFP) (Shen, et al 2013). Developmental staging followed previously published standards (Kimmel et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…We used several wellcharacterized transgenic lines including Tg(olig2:EGFP) and Tg(sox10:T-RFP) (Blasky, Pan, Moens, & Appel, 2014;H. Importantly, we found that the change in mEGFP accumulation in response to bath application of drugs is FIGURE 7 Electron micrograph analysis of myelinated axons following drug treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is a useful proxy for altered myelination in vivo in general. We used several wellcharacterized transgenic lines including Tg(olig2:EGFP) and Tg(sox10:T-RFP) (Blasky, Pan, Moens, & Appel, 2014;H. C. Park, Shin, Roberts, & Appel, 2007;Takada et al, 2010); as well as, several reporter lines made with a previously isolated regulatory sequence for mbp1a (Almeida et al, 2011;Jung et al, 2010;, to more closely assess the responses of oligodendrocyte lineage cells to GC1 and rapamycin to better understand the specific impact of each drug on myelination.…”
Section: Figurementioning
confidence: 99%